Analisis Pengaruh Kualitas Produk terhadap Kepuasan Pelanggan pada Usaha Pangan “Warunge Indah” Jakarta - Sudiharto Sudiharto; Kusairi Kusairi; Benny Hari Kusuma (CV. Syntax Corporation Indonesia, 2021)
The development of the business field has been colored by various kinds of competition in all fields, including in the field of food, technology and communication. Good quality and quality service will tend to provide more satisfaction to customers who use services in the company. The purpose of this study is to analyze the influence of product quality on customer satisfaction on the food business